Influence of Chrysoporthe deuterocubensis canker disease on the basic properties, durability, and machining of infected Eucalyptus urograndis lumber - Dahali, Rasdianah (2023)
This study investigated the influence of canker disease caused by Chrysoporthe deuterocubensis on the basic properties (physical, mechanical, and chemical composition), durability, and machining properties of Eucalyptus urograndis (E. urophylla x E. grandis) trees. Samples were collected from infected and healthy trees and grouped into four different classes, such as healthy (class 1), moderately infected (class 2), severely infected (class 3), and very severely infected (class 4). These classes have been developed according to the severity of the of the infection of C. deuterocubensis canker disease based on stem characteristics. The physical and mechanical properties were determined according to the standard test procedures specified by the ISO 13061:2014 and BS 373: 1957. The results showed that the severity of the infection had a significant impact on the physical properties of the wood. Infected wood had low EMC (10.1, 10.2, and 9.7%) and experienced less volumetric (Volsh), tangential (Tsh), and radial (Rsh) shrinkage. As a result, hydrophobicity and dimensional stability generally increased. Nevertheless, it had poorer strength compared to healthy wood. Wood from moderately and severely infected trees exhibited reduced mechanical properties, making it suitable for non-structural applications. Further investigation is needed for wood from severely infected trees to determine its suitability for structural purposes, as it obtained a higher MOR (96.4 MPa) and MOE (12.7 GPa). The primary reason for the changes in wood properties was attributed to changes in chemical constituents. The chemical composition of wood was determined according to neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL). These analyses revealed changes in the chemical composition of infected wood, with reductions in both cellulose (53.20 to 45.42%) and hemicellulose (14.13 to 13.91%) content and increased lignin (18.12 to 20.50%) and extractives (14.29 to 19.96%). Fourier transform infrared analysis (FTIR) confirmed the findings. Generally, infected wood behaves better than healthy wood in terms of durability against fungi and termites. Likewise, infected wood showed changes in durability against fungal decay (P. sanguineus and C. puteana) and termites (C. curvignathus) based on a decrease in weight loss (WL). The durability analyses were determined according to procedures outlined in the ASTM D2017 and AWPA E1-09 standard procedure. The results were presented in this study and showed it was shifted from resistance (II) to highly resistance (I) and from very poor (V) to moderately resistance (III), respectively, compared to healthy wood. The machining properties (sawing, planing, and boring) and surface roughness of the machined samples were also assessed. Prior to machining properties, the samples were prepared according to ASTM D 1666-11 standard. Overall, E. urograndis of different infection severity classes has very good machining properties, ranging from grade I (very good) to grade II (good) for each machining property tested. Meanwhile, the lowest individual board grade was attained from grade I (very good) to grade IV (poor) in the planing test. Fuzzy grain, chip grain, chip mark, and tear out are the most commonly seen physical defects. As for surface roughness, wood samples from class 1 have lower surface roughness compared to those of infected trees from classes 2, 3, and 4, which indicates a better surface quality (smoother) with only a planing and boring test giving a statistically significant result. Furthermore, C. deuterocubensis infection of stem canker had an impact on sawn timber productivity, quality, and processing performance for the logs processed in this study. However, it still has the potential to produce high-recovery and quality timber. The infection classes 2 and 4 managed to gain >40% of timber recovery. Moreover, class 2 could attain a similar grade (SELECT to SERVICEABLE and SERVICEABLE AND BETTER) to class 1. Meanwhile for the value of timber per tonnage, all infected classes 2, 3 and 4 were having a lower value than class 1 (RM 293.01 and 955.74) for SELECT AND BETTER and STANDARD AND BETTER grade. Overall, infected E. urograndis showed potential for use in the timber industry, offering durability, machining suitability, productivity, and competitive wood products.